Analisis Factor-Faktor Penyebab Kecelakaan Kerja Penggunaan Benda Tajam Atau Mesin pada Pemanen Sawit - Yeni Ayu Astuti; Susilawati, Susilawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Indonesia is a country with vast agricultural areas and the fertility of its soil is undisputed. This makes Indonesia a rich country in terms of agricultural products, especially oil palm plantations. Oil palm plantations have many advantages, especially since oil palm is a raw material that plays a strategic role in the country's economic development. However, this also avoids the risk of occupational injuries that threaten plantation workers, especially in the area of palm oil harvesting. Workplace accidents can be caused by activities involving the use of sharp tools and machinery such as dodos, egereks, ganks, axes and axes. The purpose of this study was to analyze the factors leading to occupational injuries associated with the use of sharp tools and machinery in oil palm harvesters. The results of this study indicate that there are several risk factors for workplace injury when sharps and machinery are used in oil palm harvesters, including worker knowledge level, use of personal protective equipment (PPE), and adherence to standards. indicates that there is Having it suggests that there is merit. Instruction manual (SOP)